Evaluation of left ventricular torsion in children with hypertrophic cardiomyopathy. (7th February 2013) - Prinz, Christian; Faber, Lothar; Horstkotte, Dieter; Körperich, Hermann; Moysich, Axel; Haas, Nikolaus; Kececioglu, Deniz; Thorsten Laser, Kai
Abstract: Aims: To evaluate the role of torsion in hypertrophic cardiomyopathy in children. Methods: A total of 88 children with idiopathic hypertrophic cardiomyopathy (n = 24) and concentric hypertrophy (n = 20) were investigated with speckle-tracking echocardiography and compared with age- and gender-matched healthy controls (n = 44). Results: In hypertrophic cardiomyopathy, we found increased torsion (2.8 ± 1.6 versus 1.9 ± 1.0°/cm [controls], p < 0.05) because of an increase in clockwise basal rotation (−8.7 ± 4.3° versus −4.9 ± 2.5° [controls], p < 0.001) and prolonged time to peak diastolic untwisting (3.7 ± 2.4% versus 1.7 ± 0.6% [controls] of cardiac cycle, p < 0.01), but no differences in peak untwisting velocities. Hypertrophic cardiomyopathy patients demonstrated a negative correlation between left ventricular muscle mass and torsion (r = −0.7, p < 0.001). In concentric hypertrophy, torsion was elevated because of increased apical rotation (15.1 ± 6.4° versus 10.5 ± 5.5° [controls], p < 0.05) without correlation with muscle mass. Peak untwisting velocities (− 202 ± 88 versus −145 ± 67°/s [controls], p < 0.05) were higher in concentric hypertrophy and time to peak diastolic untwisting was delayed (1.8 ± 0.8% versus 1.2 ± 0.6% [controls], p < 0.05). Conclusions: In contrast to an increased counterclockwise apical rotation in concentric hypertrophy, hypertrophic cardiomyopathy is characterised by predominantly enhanced systolic basal clockwise rotation. Diastolic untwisting is delayed in both groups. Torsion may be an interesting marker to guide patients with hypertrophic cardiomyopathy.